Lavender aromatherapy inhalation to reduce menstrual pain in teenagers - Nurul Azizah (Universitas Muhammadiyah Malang, 2019)
One way to reduce the pain of dysmenorrhea with non-pharmacological therapy is lavender aromatherapy. The purpose of this research is to find out the picture of lavender aromatherapy inhalation in decreasing the intensity of primary dysmenorrhea pain. The research method uses quasi experiment with pre-post test non equivalent control group design. Analysis using independent sample T-test. The number of repondent 30 adolescents who experience dysmenorrhea pain on 1-2 days early menstruation according to inclusion criteria. pain measurement before and after lavender aromatherapy inhalation intervention using the VAS (Visual Analog Scale) pain scale then comparing the difference in the pretest and post test values.The results showed that prior to treatment, the intensity of dysmenorrhea pain was 8.53 and after being treated in the form of lavender aromatherapy inhalation there was a decrease in pain intensity with an average of 3.77. From the statistical results using the Independent Sample T Test, P values <0.002 with 95% C.I. -1,532 - (- 0.430). This shows that the decrease in pain intensity score of dysmenorrhea after inhalation of Lavender aromatherapy (Lavendula Augustifolia) is significant. Conclusion Most teenagers experience a decrease in pain after being given inhalation lavender aromatherapy. Suggestions for further researchers so that larger respondents so the results are more representative.